As plain as spilt salt: the city as social structure in The Dispossessed. Issue 12 (2nd December 2021) - Butt, Amy
ABSTRACT: Set against the soaring skyscrapers of much canonical urban science fiction (sf), the single storey structures of Abbenay in Ursula Le Guin's The Dispossessed might be easily overlooked. But, as this paper argues, the sparse description of this city 'as plain as spilt salt' offers a rich and complex vision of architectural possibility. This paper dwells within this moment of description, drawing on personal association alongside architectural and literary theory to consider how this image of a city might cast strange new light on embedded aspects of architectural practice. It explores how the sustained consideration of the built spaces of feminist sf can provide designers with an empathetic appreciation of how the built environment reflects and informs social relations. Salt is modest, Salt is domestic, Salt is refined, Salt is anything but plain, To spill salt is to act.